Analysis of Latitudinal Variability in Sunspot Numbers from 2014 to Present - Cheiklu, Robel; Lakew, Eyoel; Ayalew, Anteneh; Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2024)
The Sunspots, which are dark patches on the sun's surface associated with significant magnetic activity, vary in number and distribution throughout time and latitudes. Understanding these fluctuations is critical for forecasting space weather and studying solar dynamics. This study aims to examine the latitudinal variability of sunspot numbers from 2014 to the present, as well as relationships with latitude and time trends. Monthly sunspot numbers from 2014 onwards were investigated. Statistical techniques such as standard deviation, Pearson correlation coefficients, ANOVA, and geographic analysis were used to study the association between latitude and sunspot numbers. The investigation indicated a standard deviation of 44.01 for sunspot numbers, indicating high fluctuation over the study period. A slight positive association (0.05) between latitude and sunspot number was discovered, with a non-significant p-value of 0.548. However, a significant relationship between year and sunspot numbers was found (F-statistic = 105.98, p-value = 3.08e-55). Sunspot numbers fluctuated significantly between -20- and 20 degrees latitude, with peaks at -45 and -10 degrees. While sunspot numbers vary over time, their association with latitude is minor. The study highlights the solar cycle's main influence on sunspot activity. Future studies should investigate additional solar factors and expand the dataset to improve knowledge of sunspot dynamics and their implications for space weather forecasting.